Leishmania mexicana pathogenicity requires flagellar assembly but not motility - Beneke, Tom; Neish, Rachel; Catta-Preta, Carolina M C; Smith, James; Valli, Jessica; McCoy, Ciaran J; Albuquerque-Wendt, Andreia; Mottram, Jeremy C; Gluenz, Eva (Virulence, 2025)
Protists of the order Trypanosomatida possess a single multifunctional flagellum, which powers cellular displacement and mediates attachment to tissues of the arthropod vector. The kinetoplastid flagellar cytoskeleton consists of a nine-microtubule doublet axoneme; further structural elaborations, which can vary between species and life cycle stages, include the assembly of axonemal dynein complexes, a pair of singlet microtubules and the extra-axonemal paraflagellar rod. The intracellular amastigote forms of Leishmania spp. build a short, non-motile cilium whose function has remained enigmatic. Here, we used a panel of 25 barcoded promastigote cell lines, including mutants lacking genes encoding flagellar assembly proteins, axonemal proteins required for normal motility, or flagellar membrane proteins to examine how these defects impact on their virulence in macrophages and mice. Mutants lacking the intraflagellar transport (IFT) protein 88 were avirulent indicating that assembly of a flagellum is necessary to allow for Leishmania survival in a mammalian host. A similarly severe loss of virulence was observed upon deletion of BBS2, a core component of the BBSome complex, which may act as a cargo adapter for IFT. By contrast, promastigotes that were unable to beat their flagella due to loss of core axonemal proteins could establish and sustain an infection and only showed a small reduction of parasite burden in vivo compared to the parental cell lines. These results confirm that flagellar motility is not necessary for mammalian infection, but flagellum assembly and the integrity of the BBSome are essential for pathogenicity.
Keywords: CRISPR screen; flagella; Flagella; Protozoan Proteins; Female; makrofágy; Virulence; myši inbrední BALB C; zvířata; virulence; myši; Mice; ženské pohlaví; Leishmania mexicana; Leishmania; motility; Animals; Macrophages; protozoální proteiny; Mice, Inbred BALB C